2021
DOI: 10.1002/chem.202103173
|View full text |Cite
|
Sign up to set email alerts
|

Metal Centers as Nucleophiles: Oxymoron of Halogen Bond‐Involving Crystal Engineering

Abstract: This review highlights recent studies discovering unconventional halogen bonding (HaB) that involves positively charged metal centers. These centers provide their filled d-orbitals for HaB, and thus behave as nucleophilic components toward the noncovalent interaction. This role of some electron-rich transition metal centers can be considered an oxymoron in the sense that the metal is, in most cases, formally cationic; consequently, its electron donor function is unexpected. The importance of Ha•••d-[M] (Ha = h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 113 publications
(202 reference statements)
0
46
0
Order By: Relevance
“…According to the IUPAC definition, 33 HaB is a net attractive interaction between an electrophilic region (σ-hole) associated with a halogen atom (HaB donor) and a nucleophilic region of the other atom or atomic group functioning as an HaB-accepting center; the electrophilic region is not necessarily electro-positive, but it should be less electronegative than the partner. Commonly used HaB acceptors include electronegative heteroatoms bearing lone pair(s) (LP(s)) 34 or positively charged d 8 metal centers exhibiting d z 2-nucleophilicity (see our recent review 35 ). Owing to the lower electronegativity of C compared to N, O, halogens, or other heteroatoms, the solid-state interaction involving the carbon lone pair is rather an exception and it is only represented by HaB between a halogen σ-hole and the isocyanide C center, [36][37][38][39][40] namely σ-(X)-hole⋯:CuNR interactions.…”
Section: Introductionmentioning
confidence: 99%
“…According to the IUPAC definition, 33 HaB is a net attractive interaction between an electrophilic region (σ-hole) associated with a halogen atom (HaB donor) and a nucleophilic region of the other atom or atomic group functioning as an HaB-accepting center; the electrophilic region is not necessarily electro-positive, but it should be less electronegative than the partner. Commonly used HaB acceptors include electronegative heteroatoms bearing lone pair(s) (LP(s)) 34 or positively charged d 8 metal centers exhibiting d z 2-nucleophilicity (see our recent review 35 ). Owing to the lower electronegativity of C compared to N, O, halogens, or other heteroatoms, the solid-state interaction involving the carbon lone pair is rather an exception and it is only represented by HaB between a halogen σ-hole and the isocyanide C center, [36][37][38][39][40] namely σ-(X)-hole⋯:CuNR interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of σ -hole interactions, halogen bonds (XBs) are among the most known and widely investigated [ 1 , 2 , 3 , 4 ]. XBs were shown to play a significant role in organocatalysis [ 5 , 6 , 7 , 8 ], crystal engineering and supramolecular chemistry [ 9 , 10 , 11 , 12 , 13 ], materials science [ 14 , 15 , 16 , 17 ], stabilization of explosives [ 18 ], drug design [ 19 , 20 ], etc. XBs R–X⋯A (X—halogen) are formed between an electron-depleted region on the continuation of the R–X bond and an electron-rich region of another atom or molecule A ( Figure 1 , bottom).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the MEP values at the Au‐atoms does not correspond to the MEP maximum in the whole series, that is likely related to the d 10 configuration of the Au(I) atom. As a matter of fact, some degree of nucleophilicty (gold as electron donor) has been recently described for neutral Au(I) complexes [62] and previously demonstrated by Esterhuysen et al . for H‐bonding and halogen bonding interactions, where the Au(I) acts as electron donor [63]…”
Section: Resultsmentioning
confidence: 67%
“…From these plots, it can be concluded that the aromatic substituent constant (σ) can be used as a general predictor of trends in regium π‐bonding. Moreover, in the Hammett's plots both EWGs and EDGs are included in the same representation and they correlate well with the standard σ values [62] …”
Section: Resultsmentioning
confidence: 70%